Effect of Pectin Contents on Properties of Biodegradable Thermoplastic Mung Bean Starch/low-density Polyethylene Blends Using Injection Molding Technique - Jutarat Prachayawarakorn (Science Faculty of Chiang Mai University, 2019)
Mechanical properties and water uptake of thermoplastic starch (TPS)/low-density polyethylene (LDPE) blend are still the main problems for applications of biodegradable polymers; therefore, properties of the TPS/LDPE blends were, then, modified using pectin, a natural gelling agent. In this study, biodegradable polymer blends; prepared from thermoplastic mung bean starch (TPMBS) and LDPE, were processed using an injection molding technique. Different contents of pectin, i.e. 0%, 2%, 4%, 6%, 8% and 10% were added into the TPMBS/LDPE blend. It was found from Fourier Transform Infrared spectroscopy (FT-IR) spectra that O-H stretching peak shifted to lower wavenumber by the addition of pectin, even with the presence of LDPE. Better phase compatibility between the TPMBS and LDPE phases, observed from Scanning Electron Microscopy (SEM) technique, was also detected by the addition of pectin. In addition, tensile properties of the TPMBS/LDPE blends were also significantly improved by the modification of pectin. Melt flow index, water absorption, thermal degradation temperature and biodegradability of different TPMBS/LDPE blends modified by pectin were also investigated.